TRANSFORMASI HIDUP PADA TOKOH-TOKOH GEREJA - Agus Widodo (P3TK, Sanata Dharma University, 2015)
Human's life never stops, it continuously changing, physically, mentally and spiritually. Physical changes are influenced by food, beverages, and various physical activities. Meanwhile, mental and spiritual changes are affected by our intellectual and liberty with which, human being are able to consider, choose and decide. Therefore, mental and spiritual changes in human are not merely natural, spontaneous and automatic process. It is a transformation that covers: change of heart, mind, willingness and attitude or action. For sure, the desired transformation is the ones which are bad to be good, and the ones which are good to be better. Therefore, the transformation itself covers changes the bad into good and into better. But, how can we transform ourselves? One way to transform is to learn from several figures in Catholic Church through the ages who have transformed their lives and become Saints.